Exploring leadership on Instagram: A visual model for online leadership analysis - Michele Martini (Journal of Digital Social Research)
Online visual communication is becoming an established and central component of citizens’ everyday life. User activity on large-scale platforms, such as Instagram, can be mapped by tracing the rise and fall of communities of practice that share different visual languages, aesthetic values and forms of leadership. Accordingly, the present study proposes an analytical model for the identification, measurement, and categorization of leadership on visual-based social networks, by asking: how does the digital performance of leaders on Instagram construct different forms of leadership? To answer this question, the Leadership Visual Performance Model (LVPM) will be presented as a theoretical tool to analyze and compare leadership performance on Social Networking Systems. While previous models mostly employed theme-based coding, this analytical tool relies on a set of structural indicators that enable a higher level of comparability across domains. To demonstrate, the LVPM will be employed to investigate the Instagram activity of Jeremy Corbyn and Boris Johnson during the 2019 UK General Election. Findings show how the LVPM indicators enable us to highlight differences in leadership style, compare them and employ them to build a typology.